Amino Acids Profile of Selected Five Genotypes of Cowpea and Mung Beans Grown in Awka, Rain Forest Zone (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
A comprehensive analysis was done at the Food Profiling Biotechnology Laboratory, National Root Crops Research Institute (NRCRI) Umudike, Umuahia to explore, as well as to compare the amino acid components of five cowpea (Vigna aunguiculata) (ITA 1,2,3,4,5) and five mung bean (Vigna radiata) (TVR 72,73,77,8,98) genotypes that were grown at the Research Farm of Crop Science and Horticulture, Nnamdi Azikiwe University. The results showed that the mung bean genotypes were high in alanine, glycine and valine while the cowpea genotypes were high in tryptophan, methionine and other sulfur-containing essential aminoacids. Both crops have relatively similar arginine, isoleucine, lysine, serine and tyrosine contents. While they reduce flatulence, the tested mung beans genotypes values for threonine, tryptophan and total sulphur-containing amino acids (methionine and cysteine) were nutritionally inadequate but this can be compensated by consuming mung bean in combination with cereals. Based on individual genotypes contents of essential amino-acids, we recommend cowpea genotypes:ITA 1,2, 5 and mung bean genotypes:TVR 72,73 and 98.
Keywords: Amino-Acids; Cowpea; Essential amino-acids; Genotypes; Mung Bean